2012
DOI: 10.1007/s00299-012-1236-x
|View full text |Cite
|
Sign up to set email alerts
|

Molecular characterization of a Cyrtochilum loxense Somatic Embryogenesis Receptor-like Kinase (SERK) gene expressed during somatic embryogenesis

Abstract: Somatic embryogenesis is crucial for the propagation of endangered Ecuadorian orchid species, among them Cyrtochilum loxense, in view of the fact that their number in nature or in collections is quite reduced. One of the genes expressed during somatic and zygotic embryogenesis is Somatic Embryogenesis Receptor-like Kinase (SERK). Despite the development of somatic embryogenesis protocols for orchids, no SERK genes have been isolated from this family. This is the first report on the isolation of a full-length o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
18
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(18 citation statements)
references
References 56 publications
0
18
0
Order By: Relevance
“…Three of these, PhSERK1, 2, and 5, showed typical SERK protein structural features, as reported for other plant species. The high sequence similarity of PhSERK1 and 2 with CnSERK (Pérez-Núñez et al, 2009), AcSERK1 and 2 (Ma et al, 2012a,b), ClSERK (Cueva et al, 2012), OsSERK (Ito et al, 2005), MtSERK1 (Nolan et al, 2003), ZmSERK1 (Baudino et al, 2001), and AtSERK1 suggests that PhSERK1 and 2 are involved in PLB formation or somatic embryogenesis, as has been proposed for orthologs from other species. Clustering of PhSERK5 with PpSERK1 and 2 ( Figure 3) also points to a similar function in embryogenesis (Albrecht et al, 2005).…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…Three of these, PhSERK1, 2, and 5, showed typical SERK protein structural features, as reported for other plant species. The high sequence similarity of PhSERK1 and 2 with CnSERK (Pérez-Núñez et al, 2009), AcSERK1 and 2 (Ma et al, 2012a,b), ClSERK (Cueva et al, 2012), OsSERK (Ito et al, 2005), MtSERK1 (Nolan et al, 2003), ZmSERK1 (Baudino et al, 2001), and AtSERK1 suggests that PhSERK1 and 2 are involved in PLB formation or somatic embryogenesis, as has been proposed for orthologs from other species. Clustering of PhSERK5 with PpSERK1 and 2 ( Figure 3) also points to a similar function in embryogenesis (Albrecht et al, 2005).…”
Section: Discussionmentioning
confidence: 85%
“…OsSERK1 is thought to be partially responsible for mediating defense signal transduction and has a basic role in rice somatic embryogenesis (Hu et al, 2005). More homologs of SERK have been identified in several plant species, including Dactylis glomerata (Somleva et al, 2000), Medicago truncatula (Nolan et al, 2003(Nolan et al, , 2009, Ocotea catharinensis (Santa-Catarina et al, 2004), Helianthus annuus (Thomas et al, 2004), Theobroma cacao (Santos et al, 2005), Citrus unshiu (Shimada et al, 2005), Triticum aestivum (Singla et al, 2008), Vitis vinifera (Schellenbaum et al, 2008), Solanum tuberosum (Sharma et al, 2008), Cocos nucifera (Perez-Núñez et al, 2009), Lactuca sativa (Santos et al, 2009), Rosa hybrida (Zakizadeh et al, 2010), Musa acuminata (Huang et al, 2010), Secale cereale (Gruszczyńska and Rakoczy-Trojanowska, 2011), Glycine max (Yang et al, 2011), Cyclamen persicum (Savona et al, 2012), Ananas comosus (Ma et al, 2012a,b), and Cyrtochilum loxense (Cueva et al, 2012). These reports all point to SERK as a specific marker of embryogenic competence during morphogenesis induction.…”
Section: Introductionmentioning
confidence: 99%
“…In several species, SERK expression has been linked to acquisition of embryogenic competence Thomas et al, 2004;Pérez-Núñez et al, 2009;Cueva et al, 2012;Talapatra et al, 2014). Monitoring of expression during somatic embryogenesis in in vitro cultures revealed that CaSERK was most strongly expressed in embryogenic callus.…”
Section: Discussionmentioning
confidence: 99%
“…The involvement of SERK proteins in regulating somatic embryogenesis was first described for DcSERK in embryogenic cell suspension cultures of carrot more than 15 years ago (Schmidt et al, 1997). Since then SERK gene homologs have been identified and their role in mediating somatic embryogenesis demonstrated in several monocot and dicot species such as Arabidopsis thaliana , Medicago truncatula (Nolan et al, 2003), Triticum aestivum (Singla et al, 2008), Vitis vinifera (Maillot et al, 2009), Cocos nucifera (Pérez-Núñez et al, 2009), Ananas comosus (Ma et al, 2012) and Cyrtochilum loxense (Cueva et al, 2012). Moreover, a gymnosperm SERK homolog has recently been discovered and its association with somatic embryogenesis was shown (Steiner et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…LRR-RLKs are divided into 13 subclasses according to the structure and quantity of different extracellular LRRs (Gou et al, 2010) 2010, and SERK belongs to the second subclass (Shiu and Bleecker, 2001). The protein structure of SERK begins with a signal N-terminal peptide followed by one leu-zipper domain, five LRRs, one ser-pro-ro (SPP) motif, one single transmembrane (TM) domain, three conserved serine/threonine kinase subdomains, and one C-terminal leucine-rich domain (Cueva et al, 2012).…”
Section: Introductionmentioning
confidence: 99%